2017
DOI: 10.1101/143453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Back-translating a rodent measure of negative bias into humans: the impact of induced anxiety and unmedicated mood and anxiety disorders

Abstract: Negative affective biases are a core feature in the development and maintenance of mood and anxiety disorders and a key target for treatment development. However, recent years have seen a number of promising pre-clinical interventions fail to translate into clinical efficacy in humans. One reason for this is that, in some cases, the animal models inadequately scale-up to human symptoms. To address this, here we directly adapt-i.e. back-translate -a rodent measure of negative affective bias into humans, and exp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Another study looking at models of economic decision making under uncertainty (Figure 1C) suggested that anxiety was associated with risk but not with loss aversion (Charpentier et al, 2016). Finally, there is evidence that high trait anxiety is associated with increased boundary separation and nondecision time on the drift diffusion model (White et al, 2010) rather than the reduced drift rate seen in anhedonia (although see Aylward, Hales, Robinson, & Robinson, 2017, for potential evidence of drift rate changes in anxiety disorders).…”
Section: Five Questions For Future Researchmentioning
confidence: 99%
“…Another study looking at models of economic decision making under uncertainty (Figure 1C) suggested that anxiety was associated with risk but not with loss aversion (Charpentier et al, 2016). Finally, there is evidence that high trait anxiety is associated with increased boundary separation and nondecision time on the drift diffusion model (White et al, 2010) rather than the reduced drift rate seen in anhedonia (although see Aylward, Hales, Robinson, & Robinson, 2017, for potential evidence of drift rate changes in anxiety disorders).…”
Section: Five Questions For Future Researchmentioning
confidence: 99%
“…A novel version of this task has also been developed which utilizes rodent natural investigative behaviours rather than lever pressing, which recapitulate similar effects of affective state manipulations on judgement bias [108]. Further, recent studies have evaluated translational human versions of this task, which link negative biases with pathological anxiety [95,109,110].…”
Section: Rodent Behavioural Assays Of Affective Biasmentioning
confidence: 99%